A dual-omics approach for profiling plant responses to biostimulant applications under controlled and field conditions - Baghdadi, Ali; Della Lucia, Maria Cristina; Borella, Matteo; Bertoldo, Giovanni; Ravi, Samathmika; Zegada-Lizarazu, Walter; Chiodi, Claudia; Pagani, Elena; Hermans, Christian; Stevanato, Piergiorgio; Nardi, Serenella; Monti, Andrea; et al. (Frontiers in Plant Science, 2022)
A comprehensive approach using phenomics and global transcriptomics for dissecting plant response to biostimulants is illustrated with tomato (Solanum lycopersicum cv. Micro-Tom and Rio Grande) plants cultivated in the laboratory, greenhouse, and open field conditions. Biostimulant treatment based on an Ascophyllum nodosum extract (ANE) was applied as a foliar spray with two doses (1 or 2 l ha-1) at three different phenological stages (BBCH51, BBCH61, and BBCH65) during the flowering phase. Both ANE doses resulted in greater net photosynthesis rate, stomatal conductance, and fruit yield across all culture conditions. A global transcriptomic analysis of leaves from plants grown in the climate chamber, revealed a greater number of differentially expressed genes (DEGs) with the low ANE dose compared to the greater one. The second and third applications induced broader transcriptome changes compared to the first one, indicating a cumulative treatment effect. The functional enrichment analysis of DEGs highlighted pathways related to stimulus-response and photosynthesis, consistent with the morpho-physiological observations. This study is the first comprehensive dual-omics approach for profiling plant responses to biostimulants across three different culture conditions.